Sistem Pengarsipan Surat Masuk dan Surat Keluar Berbasis Visual Basic di Kantor Bapperida Provinsi Papua Tengah - Wisna Bara’ Padalingan; Kristia Yuliawan (Jurnal Teknologi dan Informatika, 2024)
The development of a letter archiving system based on Visual Basic at the Bapperida Office of Central Papua Province aims to enhance the efficiency and effectiveness of letter archive management. This system addresses various issues found in manual archiving, such as slow processes, difficulty in searching, risks of document damage and loss, and the large space required for storage. With features like automation, advanced search, digital storage, and access control, this system enables faster, more accurate, and safer archiving processes. The use of the prototype method ensures the system meets user needs through continuous iterations. The research results indicate that this system successfully improves the quality of information services, supports good governance principles, and provides significant storage space savings. Overall, this system is expected to better and more efficiently support the execution of organizational tasks and functions.